Influence of heat treatment on the mechanical properties of CrNi stainless steel orthodontic wires - Clariana Hoehne Sepúlveda; Sávio Morato de Lacerda Gontijo; Leandro de Arruda Santos; Alexandre Fortes Drummond; Leonardo Foresti Soares de Menezes; Leniana Santos Neves; Esdras Campos França (Dental Press Journal of Orthodontics)
ABSTRACT Introduction: The heat treatment of stainless steel wires is a routine clinical procedure adopted by many dentists in order to relieve the stress caused after performing bends in the archwire. Objective: This study aimed to evaluate the influence of heat treatment of stainless steel archwires with a rectangular section of 0.016 x 0.022’-in. Methods: For analysis of the dimensional stability, the anterior and posterior dimensions of forty 0.016 x 0.022-in stainless steel orthodontic archwires without heat treatment and 30 days after heat treatment were evaluated. For analysis of the mechanical properties, 12 stainless steel wire segments with the same rectangular section without heat treatment and 30 days after heat treatment were tested through tensile strength and strain tests. To evaluate if there were differences between the anterior and posterior dimensions, the results were analyzed by the Student’s t-test. To compare the tensile strength and strain between the groups, the ANOVA test was used. The level of significance adopted was 95% (p< 0.05). Results: The heat treatment did not stop the expansion of archwires 30 days after their preparation, and there was no statistical difference in the tensile strength and strain tests with and without heat treatment. Conclusion: From the findings of this study, it can be conclude that the mechanical behavior of heat-treated stainless steel archwires is similar to that of archwires not subjected to heat treatment.